Platelets in HIV: A Guardian of Host Defence or Transient Reservoir of the Virus? - Pretorius, Etheresia (Frontiers in Immunology, 2021)
The immune and inflammatory responses of platelets to human immunodeficiency virus 1 (HIV-1) and its envelope proteins are of great significance to both the treatment of the infection, and to the comorbidities related to systemic inflammation. Platelets can interact with the HIV-1 virus itself, or with viral membrane proteins, or with dysregulated inflammatory molecules in circulation, ensuing from HIV-1 infection. Platelets can facilitate the inhibition of HIV-1 infection via endogenously-produced inhibitors of HIV-1 replication, or the virus can temporarily hide from the immune system inside platelets, whereby platelets act as HIV-1 reservoirs. Platelets are therefore both guardians of the host defence system, and transient reservoirs of the virus. Such reservoirs may be of particular significance during combination antiretroviral therapy (cART) interruption, as it may drive viral persistence, and result in significant implications for treatment. Both HIV-1 envelope proteins and circulating inflammatory molecules can also initiate platelet complex formation with immune cells and erythrocytes. Complex formation cause platelet hypercoagulation and may lead to an increased thrombotic risk. Ultimately, HIV-1 infection can initiate platelet depletion and thrombocytopenia. Because of their relatively short lifespan, platelets are important signalling entities, and could be targeted more directly during HIV-1 infection and cART.